Haemoglobin, Serum Iron Level and Cardiovascular Status in Advanced Stages of Chronic Kidney Disease Patients admitted in A Tertiary Care Centre - Ali, Md Yousuf; Alam, Md Ehsanul; Rahman, Aminur; Majid, Nadira (Bangladesh Journal of Medicine, 2021)
Background: Anaemia due to advanced stages of chronic kidney disease increases morbidity of patients. Early detection and correction of anaemia may be helpful in preventing the progress of the disease & its cardiovascular outcomes. The objective of this study was to evaluate hemoglobin, serum iron level and cardiovascular status in advanced of CKD patients. Methods: This was a cross sectional observational study on 150 cases of diagnosed advanced stages (3B,4 &5) of CKD patients in indoor of department of medicine of Mitford Hospital, Dhaka from July 2019 to January 2020. Convenience sampling was done. Data were analyzed with SPSS 26. Results: Total number of patients were 150. Male were 93 (62%) and female were 57 (38%). The mean (±SD) age was 55.22 (±10.30) years (range 33 - 75 years). Among the study subjects 38% had history of blood transfusion, 60% had history of iron supplementation and 12% subjects received erythropoietin. Mean (±SD) haemoglobin level was 7.61 (±2.54) g/dl. Seventy percent of the study subjects had haemoglobin level < 9 g/dl and rest had ³9 g/dl. Significant difference was found in between these two groups (p = 0.036). In the present study, mean (±SD) serum iron level was 15.59 (±07.39) μmol/l. In 46% of the study subjects, iron level was 7.3μ mol/l and 52% had iron level between 7.3 to 23.6 μmole/ lit. Mean (± SD) ferritin level of the study subjects was 155.22 (±92.32) ng/ ml. In 58% of the study subjects ferritin level was < 100ng/ ml and 42% had >100 ng/ml. Significant difference was found in between these two groups (p = 0.041) (Table-IV). Ferritin level had significant positive relationship with blood transfusion, iron and erythropoietin supplementation on logistic regression analysis. Haemoglobin and serum ferritin level was positively correlated with eGFR of the study subjects. Statistical analysis showed significant relationship between eGFR with haemoglobin and serum ferritin. Forty six percent of the study subjects had Transferrin saturation (TSAT) level below 20%. Fifty four percent subjects had a TSAT level above 20%. Significant difference was found in between these two groups (p = 0.001). In correlation analysis, haemoglobin, serum ferritin and TSAT level in the study subjects had negative relationship with duration of CKD in years. Relationship of haemoglobin and TSAT level with duration of CKD was statistically significant. In correlation analysis, serum TIBC level had negative relationship with haemoglobin level which was statistically significant. Serum iron, ferritin and TSAT level in the study subjects were positively correlated with haemoglobin level. Relationship of haemoglobin with serum iron level and TSAT level was statistically significant. Twenty percent of the study subjects had peripheral vascular disease, 111 (74%) of the study subjects had hypertension, 66 (44%) had ischaemic heart disease, 27 (18%) had a history of acute myocardial infarction, 24 (16%) had chronic heart failure, 93 (62%) had dyslipidemia and 27 (18%) patients had history of stroke. Conclusion: In this study it was observed that TSAT appears to be a more useful indicator for measuring the frequency of iron deficiency than serum iron, TIBC and serum ferritin. The cardiovascular comorbidities plagued significant number of patients with advanced CKD. Bangladesh J Medicine July 2022; 33(1) : 34-39